2012
DOI: 10.1515/ijdhd-2012-0036
|View full text |Cite
|
Sign up to set email alerts
|

Development of a positive youth development subject in a university context in Hong Kong

Abstract: A survey of the literature shows that there are worrying developmental issues among university students in Hong Kong. Unfortunately, universal adolescent prevention and positive youth development programs specifi cally designed for university students are grossly lacking in Hong Kong. With reference to the positive youth development approach, it is argued that promotion of intrapersonal competencies and interpersonal relationship skills among university students is an important strategy to facilitate holistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
(9 reference statements)
3
19
0
Order By: Relevance
“…Findings of the present study add to the previous results by showing the beneficial effects of a leadership course on promoting the holistic development among the firstyear Hong Kong college students [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The results of the current study showed that participants scored higher in several composite and subscale measures over the course of the semester.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Findings of the present study add to the previous results by showing the beneficial effects of a leadership course on promoting the holistic development among the firstyear Hong Kong college students [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The results of the current study showed that participants scored higher in several composite and subscale measures over the course of the semester.…”
Section: Discussionsupporting
confidence: 79%
“…This subject attempts to help students develop their intra-and interpersonal qualities through understanding the concepts and qualities of effective leadership and acquiring self-reflection skills in their daily lives. To meet the general university requirements (GURs), all full-time students admitted to the 4-year undergraduate curriculum are required to take a 3-credit course satisfying the area of leadership and intrapersonal development [16].…”
Section: Introductionmentioning
confidence: 99%
“…There are several research fi ndings suggesting that the subject can promote holistic development of the students (14,15) . First, objective outcome evaluation fi ndings based on a pre-test/post-test pre-experimental design showed that students showed improved holistic development and psychosocial competencies after taking the subject (16) .…”
Section: Introductionmentioning
confidence: 99%
“…Third, process evaluation findings showed that the implementation quality was good and program adherence was high. Fourth, different qualitative evaluation methods suggest that the subject was beneficial to the development of the students taking this subject [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%